Effect of Loan to Deposit Ratio (LDR) and BOPO on Profitability on PT BPR Bali Ambassador for the Year 2014-2018 - Ni Made Rusmini; Ade Maharini Adiandari (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Profitability is the ability or ability of the bank to obtain profits or profits. The problem of profitability is very important because the bank's income is the main target that must be achieved by the bank because the main purpose of the bank is to achieve profit or profit. The higher the bank's profitability, the better the bank's performance. The formulation of the problem in this study is: whether the Loan to Deposit Ratio (LDR) and Operational Income Operating Costs (BOPO) simultaneously or partially affect the profitability of PT. BPR. Duta Bali for the period 2014-2018? This study aims to determine the effect simultaneously or partially between the Loan to Deposit Ratio (LDR) and Operational Income Operating Costs (BOPO) to Profitability at PT. BPR. Duta Bali for the period 2014-2018. The technique of taking samples in this study uses judgmental sampling. Data were analyzed using classical assumption test, multiple linear regression analysis, Determination analysis, simultaneous significance test (F-test) and partial significance test (t-test). The results of the study indicate that the Loan to Deposit Ratio has a positive and insignificant effect on Profitabiltas. Operational Costs Operational Income has a significant positive effect on profitability. Loan to Deposit Ratio and Operational Costs Operational Income has a significant effect on profitability at PT. BPR. Duta Bali for the period 2014-2018.